Research on the Impact of the Brand Image of Geographically Iconic Agricultural Products on Consumers’ Purchase Intention: A Case Study of Guangxi Shatangju - Pang, Zhaofu (Business Administration and Economics Review, 2025)
The development of geographical indication agricultural products is an important pathway for China to achieve rural revitalization; additionally, agriculture still plays an important role in international competitiveness and regional industrial development. This study takes consumers who have purchased geographical indication agricultural products as the research object and explores the impact of geographical indication agricultural product brand image on consumer purchase intentions from the perspectives of industry scale, natural environment, human environment, product quality, and production method. Through a questionnaire survey and data analysis, the study shows that all brand dimensions have a significant positive impact on consumer purchase intentions, while perceived value has a positive moderating effect between them, indicating that the richer the product image and quality information, the more significant the impact of brand image on purchase intentions. Finally, the conclusions drawn from this study can provide guidance for the government and farmers to optimize brand image construction; moreover, consumers can correctly identify and purchase geographical indication agricultural products.